Alzheimer’s Disease and Cancer: When Two Monsters Cannot Be Together - Majd, Shohreh; Power, John; Majd, Zohreh (Frontiers in Neuroscience, 2019)
Alzheimer’s disease (AD) and cancer are among the leading causes of human death around the world. While neurodegeneration is the main feature of AD, the most important characteristic of malignant tumours is cell proliferation, placing these two diseases in opposite sides of cell division spectrum. Interestingly, AD and cancer’s pathologies consist of a remarkable common feature and that is the presence of active cell cycle in both conditions. In an in vitro model of primary adult neuronal culture, we previously showed that treating cell with beta amyloid forced neurons to start a cell cycle. Instead of cell division, however neuronal cell cycle was aborted and a massive neurodegeneration was left behind as the consequence. A high level of cell cycle entry, which is a requirement for cancer pathogenesis, was reported in clinically diagnosed cases of AD, leading to neurodegeneration. The diverse clinical manifestation of a similar etiology, have puzzled researchers for many years. In fact, the evidence showed an inverse association between AD and cancer prevalence, suggesting that switching pathogenesis toward AD protects patients against cancer and vice versa. In this minireview, we discussed the possibility of involvement of cell proliferation and survival dysregulation as the underlying mechanism of neurodegeneration in AD, and the leading event to develop both disorders’ pathology. As examples, the role of phosphoinositide 3 kinase/Akt/ mammalian target of rapamycin (PI3K/Akt/mTOR) signaling pathway in cell cycle re-entry and blocking autophagy are discussed as potential common intracellular components between AD and cancer pathogenesis, with diverse clinical diagnosis.